Toll-like receptor 4-mediated nuclear factor kappa B activation is essential for sensing exogenous oxidants to propagate and maintain oxidative/nitrosative cellular stress. - Rajendra Karki (Public Library of Science (PLoS), 2013)
The mechanism(s) by which cells can sense exogenous oxidants that may contribute to intracellular oxidative/nitrosative stress is not clear. The objective of this study was to determine how cells might respond to exogenous oxidants to potentially initiate, propagate and/or maintain inflammation associated with many human diseases through NF-κB activation. First, we used HEK-Blue cells that are stably transfected with mouse toll-like receptor 4 (mTLR4) or mouse TLR2. These cells also express optimized secreted embryonic alkaline phosphatase (SEAP) reporter gene under the control of a promoter inducible by NF-κB transcription factor. These cells were challenged with their respective receptor-specific ligands, different pro-oxidants and/or inhibitors that act at different levels of the receptor signaling pathways. A neutralizing antibody directed against TLR4 inhibited responses to both TLR4-specific agonist and a prooxidant, which confirmed that both agents act through TLR4. We used the level of SEAP released into the culture media due to NF-κB activation as a measure of TLR4 or TLR2 stimulation. Pro-oxidants evoked increased release of SEAP from HEK-Blue mTLR4 cells at a much lower concentration compared with release from the HEK-Blue mTLR2 cells. Specific TLR4 signaling pathway inhibitors and oxidant scavengers (anti-oxidants) significantly attenuated oxidant-induced SEAP release by TLR4 stimulation. Furthermore, a novel pro-oxidant that decays to produce the same reactants as activated phagocytes induced inflammatory pain responses in the mouse orofacial region with increased TLR4 expression, and IL-1β and TNFα tissue levels. EUK-134, a synthetic serum-stable scavenger of oxidative species decreased these effects. Our data provide in vitro and related in vivo evidence that exogenous oxidants can induce and maintain inflammation by acting mainly through a TLR4-dependent pathway, with implications in many chronic human ailments.